In Silico Molecular Docking, Synthesis and Preliminary Evaluation of Antibacterial Activity of Levofloxacin Carboxamides with Certain Amino Acids - Sarah Abdul-Razzaq makki; Shakir M Alwan; Mayada H. Al-Qaissy (College of Pharmacy / Mustansiriyah University, 2023)
Levofloxacin carboxamides with certain amino acids were prepared through an amide linkage to the amino acid (glycine, histidine, or serine). These carboxamides were subjected to an in silico molecular docking evaluation on   DNA gyrase to predict their antibacterial activity using the GOLD suite. The binding affinities were very significant and encouraged the synthesis of the suggested carboxamides for intensive evaluation. These carboxamides were also subjected to Swiss ADME software to predict their ADME parameters. Levofloxacin carboxamides were prepared in high yield, and their chemical structures were confirmed by spectral analysis, such as 1H-NMR, 13C-NMR and FT-IR spectroscopy. Antibacterial activities were evaluated for the new carboxamides against two G-ve (Klebsiella and P. aeruginosa) and one G+ve (Streptococcus pneumonia) bacteria. When compared to levofloxacin, all of the synthesized carboxamides 1-3 demonstrated good activity against three types of bacteria. These carboxamides showed significant antibacterial activities against S. pneumoniae and lower activities against Klebsiella.